Output-input hybrid passive filter design for electric vehicle charging station - Khudher, Shaker Mahmood; Aris, Ishak; Othman, Mohammad Lutfi; Mailah, Nashiren Farzilah (College of Engineering, University of Mosul, 2021)
The impact of electric car charging stations on power grid harmonics is growing as their existence continues to expand and creates harmonic distortion in the power system. At the same time, the quality of charging current and voltage through the process of charge becomes inferior. Therefore, reduction of output ripple factor (RF) and mitigation of input current harmonics is vital in this situation. This paper presents the design of the output filter and three kinds of shunt passive input filters to decrease the present harmonics generated in the industrial power scheme by the charging stations. The simulation software MATLAB/Simulink was used. Results were acquired before and after installation of filters and after installation of filters, it was found that the percentage RF of output current, voltage, and the percentage THD of the input current is reduced to match the set standards.